Escapees : the history of Jews who fled Nazi deportation trains in France, Belgium, and the Netherlands - Fransecky, Tanja von (Berghahn Books, 2019)
Of the countless stories of resistance, ingenuity, and personal risk to emerge in the years following the Holocaust, among the most remarkable, yet largely overlooked, are those of the hundreds of Jewish deportees who escaped from moving trains bound for the extermination camps. In France, Belgium, and the Netherlands alone over 750 men, women and children undertook such dramatic escape attempts, despite the extraordinary uncertainty and physical danger they often faced. Drawing upon extensive interviews and a wealth of new historical evidence, Escapees gives a fascinating collective account of this hitherto neglected form of resistance to Nazi persecution.